Pribumisasi Dalam Pandangan Abdurahman Wahid - A. Soheh Mukarom (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2017)
Indigenization (pribumisasi) of Islam in Java can not be compared to syncretism because it only involves local culture in defining Islamic laws without changing its substances to meet local culture. Indigenization as Wahid means is how Islamic doctrines are interpreted so that local culture is valid in terms of Islamic jurisprudences. On the other hand, syncretism is mixing two or more religious beliefs and as a result it makes another and new form of belief as exemplified in ritual practice of a thousand deity temple in India.